Burger’s medicinal chemistry and drug discovery - Burger, Alfred (Hoboken, N.J., 2003)
This Sixth Edition of Burgers Medicinal Chemistry and Drug Discovery has been expanded to six volumes: Volume 1: Drug Discovery Volume 2: Drug Discovery and Drug Development Volume 3: Cardiovascular Agents and Endocrines Volume 4: Autocoids, Diagnostics, and Drugs from New Biology Volume 5: Chemotherapeutic Agents Volume 6: Nervous System Agents This is Volume 5: Chemotherapeutic Agents, of Burger's Medicinal Chemistry and Drug Discovery, 6th Edition. This new volume contains critical new chapters on Molecular Biology of Cancer, Synthetic Anti-angiogenic Agents and Selective Toxicities
Keywords: Pharmaceutical chemistry,Drug development,Hóa dược,Điều chế thuốc